2019
DOI: 10.1002/ar.24075
|View full text |Cite
|
Sign up to set email alerts
|

The Mussel Mytilus galloprovincialis in the Bay of Naples: New Insights on Oogenic Cycle and Its Hormonal Control

Abstract: The aim of the present article was to investigate the oogenic cycle of Mytilus galloprovincialis sampled in the Bay of Naples, and to immunolocalize 3β‐hydroxysteroid dehydrogenase (3β‐HSD), 17β‐hydroxysteroid dehydrogenase (17β‐HSD), and P450 aromatase, enzymes involved in the synthesis of two sex hormones: testosterone and 17β‐estradiol. We demonstrate that the oogenic cycle starts in late summer‐early fall and continues in early winter when the first event of spawning occurs; other spawning events take plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…In the testis, they are primarily produced in Leydig and Sertoli cells, where they are synthesized from a common precursor, the cholesterol, via a series of enzyme‐catalyzed reactions (Miller, ). However, in recent years it has been showed that germ cells also produce sex hormones (Agnese et al, ; Carreau et al, ; Prisco et al, ; Rosati, Agnese, et al, ; Rosati, Agnese, Abbagnale, et al, ; Rosati, Santillo, et al, ). Indeed, more recently, in some seasonal breeding, as the bivalve mollusk Mytilus galloprovincialis and the squamous reptile Podarcis sicula, we highlighted that not only the somatic cells, but also the germ cells are involved in the steroidogenesis synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…In the testis, they are primarily produced in Leydig and Sertoli cells, where they are synthesized from a common precursor, the cholesterol, via a series of enzyme‐catalyzed reactions (Miller, ). However, in recent years it has been showed that germ cells also produce sex hormones (Agnese et al, ; Carreau et al, ; Prisco et al, ; Rosati, Agnese, et al, ; Rosati, Agnese, Abbagnale, et al, ; Rosati, Santillo, et al, ). Indeed, more recently, in some seasonal breeding, as the bivalve mollusk Mytilus galloprovincialis and the squamous reptile Podarcis sicula, we highlighted that not only the somatic cells, but also the germ cells are involved in the steroidogenesis synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…It is to be noted that the ER1 and ER2 expression within the growing oocytes, follicular, and adipogranular cells overlaps with the expression of the mRNA for vitellogenin, strongly suggesting that in Mytilus , as in vertebrates studied so far, the expression of vitellogenin is under the control of estrogens and is mediated by receptors. It is worth to note that the same cells are equipped with the key enzyme that control the sex hormone synthesis (Rosati, Agnese, et al, ; Rosati, Prisco, et al, ). Considering that ER1 is up and downstream factors activated by downstream factors via feedback mechanisms (Horard & Vanacker, ; Nagasawa et al, ), whereas ER2 is responsive to estrogens, it is quite probably that in M. galloprovincialis ER1 and ER2, differently attend in the gametogenesis: ER1 mainly in the spawning and ER2 in the oocyte growth, particularly in vitellogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty‐five females for each phase of the reproductive cycle (Stages 0–III; Dunker et al, 2008) were used. Specimens were collected in the Bay of Naples as previously reported for the males (Prisco, Agnese, De Marino, Andreuccetti, & Rosati, ; Rosati, Prisco, et al, ). The ovaries, excised using sterile RNase‐free dissecting equipment, were either frozen on dry ice and stored at −80°C or fixed for 24 hr in Bouin's solution, dehydrated with graded ethanol and embedded in paraffin wax.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations